2020
DOI: 10.3390/ijerph17103745
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian Health Care Workers’ Insights into and Responses to Intimate Partner Violence in Pregnancy—A Qualitative Study

Abstract: Violence against women is a global pandemic, with the potential to spread through generations. Intimate partner violence has impacts on women’s sexual, reproductive, and psycho-social health. It can occur during pregnancy and adversely affect the health of both mother and child. Health care workers involved in antenatal care can have a unique role in identifying intimate partner violence and in intervening, preventing, and mitigating its consequences. In this study, the objective was to explore Ethiopian healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 76 publications
6
10
0
2
Order By: Relevance
“…Disclosure is an opportunity for empowering actions that assist abused women in receiving support, care and reduce intimate partner violence [51]. Gashaw et al (2020) recommended mothers' empowerment through education, income generating activities, and employment [52]. Through psychological counselling abused women found that they are able to find appropriate solutions to disclose violence and solve intimate partner violence through their empowerment and positive negotiations with their husbands.…”
Section: Discussionmentioning
confidence: 99%
“…Disclosure is an opportunity for empowering actions that assist abused women in receiving support, care and reduce intimate partner violence [51]. Gashaw et al (2020) recommended mothers' empowerment through education, income generating activities, and employment [52]. Through psychological counselling abused women found that they are able to find appropriate solutions to disclose violence and solve intimate partner violence through their empowerment and positive negotiations with their husbands.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of IPV in Ethiopia, focused efforts are required by government and other stakeholders to change the cultural, structural, institutional and social barriers to mitigate impact and reduce occurrence of IPV. The perspective of community stakeholders and healthcare providers related to IPV underscore these challenges [ 58 , 59 ]. Taking into consideration other recent studies addressing the effect of IPV on maternal health and healthcare utilization [ 25 , 60 ], it is evident that in order to reach several of the health care and political goals set in Ethiopia, IPV prevention has to be high on the agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Disclosure is an opportunity for empowering actions that assist the abused women receiving support, care and reduce intimate partner violence (51,52). Gashaw et al (2020) recommended mothers' empowerment through education, income generating activities, and employment (53). Through psychological counselling abused women found that they are able to nd appropriate solutions to disclose violence and solve intimate partner violence through their empowerment and positive negotiations with their husbands.…”
Section: Discussionmentioning
confidence: 99%